A porous silicon-carbon composite microsphere and its preparation method and application

Porous silicon-carbon composite microspheres prepared by droplet microfluidic technology solve the problem of volume change and insufficient conductivity of the negative electrode material of lithium-ion battery during charging and discharging, achieve high specific capacity and good cycle characteristics, and promote lithium High energy density development of ion batteries.

CN115966685BActive Publication Date: 2024-12-31SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310025234.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-09
Publication Date
2024-12-31
Estimated Expiration
2043-01-09

AI Technical Summary

Technical Problem

The theoretical capacity of the negative electrode material of lithium-ion batteries is limited. Volume changes in silicon materials during charging and discharging lead to structural fracture and unstable solid electrolyte interface, affecting the cycling characteristics and conductivity of the battery.

Method used

Silicon-carbon composite microspheres with porous structures were prepared by droplet microfluidic technology. By mixing CNT-COOH, SiNPs and PS nanoparticles, microfluidic technology was used to form microemulsion droplets, and calcining under an inert atmosphere was used to remove PS nanoparticles. Silicon-carbon composite microspheres with narrow particle size distribution and rich pores are formed, and are used in the negative electrode of lithium-ion batteries.

Benefits of technology

It effectively alleviates the volume expansion of silicon, improves the conductivity and ion transmission channels, significantly improves the specific capacity, rate performance and cycle stability of lithium-ion batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115966685B_ABST
    Figure CN115966685B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and specifically provides a porous structure silicon-carbon composite microsphere and a preparation method and application thereof. By using an aqueous solution obtained by mixing CNT-COOH, SiNPs and PS nanoparticles as a precursor solution, a span 80 n-hexadecane solution as a continuous phase, adjusting the flow rates of the continuous phase and the dispersed phase, so that the dispersed phase is shear-emulsified by the continuous phase in a microfluidic device to form microemulsion droplets of uniform size, and obtaining microspheres after drying, the microspheres are calcined under an inert atmosphere, and the PS nanoparticles are removed to obtain silicon-carbon composite microspheres. This technology is not only simple and effective, but also the prepared silicon-carbon composite material has uniform size and abundant pores. The volume expansion of silicon during the charge and discharge process can be alleviated to ensure the integrity of the material structure, while providing a transport channel for ions and improving conductivity. When the silicon-carbon composite material is applied to the negative electrode of a lithium ion battery, the battery exhibits excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a porous silicon-carbon composite microsphere and a preparation method and application thereof. Background Art

[0002] With the demand for high capacity and long battery life of lithium-ion batteries in new energy vehicles, communications and portable devices, the development of lithium-ion batteries has reached a bottleneck. For the negative electrode, the currently widely used negative electrode materials are various carbon materials based on graphite, with a theoretical capacity of only 372mAh / g. In actual application, it is close to the theoretical capacity, and it is difficult to meet higher capacity requirements. Therefore, the research on high specific capacity negative electrode active materials has become a general trend. Among them, the theoretical capacity of silicon materials is much higher than that of graphite carbon materials, reaching 4200mAh / g, and the resources are relatively abundant, up to 26.3% in the earth's crust, and it is one of the main choices for the next generation of high energy density lithium-ion battery negative electrode materials.

[0003] However, the practical application of silicon anodes is currently hindered by multiple obstacles. The main reason is that the volume of silicon changes greatly (about 300%) after complete lithium removal, and expansion / contraction stress is generated during repeated lithium insertion / de-lithiation, resulting in severe fracture of the silicon material. This leads to the formation of an unstable solid electrolyte interface film (SEI) on the silicon surface, which continuously consumes electrolyte, resulting in rapid irreversible capacity loss and low initial coulombic efficiency. In addition, the inherent low conductivity of silicon (10 -5 ~10 -3 S / cm) and low lithium ion diffusion coefficient (10 -14 ~10 -13 cm 2 / s), which also significantly affects the rate performance and Coulomb efficiency of the silicon electrode.

[0004] In view of the above problems, the structural design of silicon-carbon composites can effectively buffer the change of silicon volume, improve the conductivity, and provide channels for ion transport. Si / C composites prepared by spray drying, chemical vapor deposition (CVD), pyrolysis and other methods focus on nano- or sub-nanoscale silicon. Although these methods can achieve uniform coating or modification of silicon nanoparticles, they also have the disadvantages of complex operation and expensive equipment. Therefore, it is still a challenge to develop a simple micron-scale structural adjustment strategy, especially to improve the performance of microspheres.

[0005] Microfluidics has emerged as a promising structure-tuning technology that can generate monodisperse single / multi-emulsion droplets while enabling precise control of the chemical composition and physical structure of the droplets and the particles inside, capable of producing highly uniform materials in the range of 0.1-1000 μm. Monodisperse colloidal nanoparticles in microemulsions are confined to spherical droplets due to the action of surfactants, and functional colloidal superparticles (SPs) such as icosahedrons, dihedrons, and single-face-centered cubic clusters gradually form as the water evaporates. SPs offer a wide range of attractive properties, one of the key features being the huge structural diversity that can be simply and precisely tuned by the constituent colloidal building blocks, the size of the enclosed droplets, and the kinetics of the consolidation process. Their application in regulating the structure of silicon-carbon composite microspheres has not been reported. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a porous structure silicon-carbon composite microsphere and its preparation method and application. The present invention adopts droplet microfluidic technology to design the structure of silicon-carbon composite materials. The prepared silicon-carbon microsphere has a narrow particle size distribution and a unique structure. When it is applied to the negative electrode of a lithium-ion battery, it can not only alleviate the volume expansion of silicon during the charging and discharging process to ensure the integrity of the material structure and improve the service life, but also provide a transport channel for ions, improve conductivity, and make the lithium-ion battery show higher specific capacity, better cycle characteristics and safety, realize the excellent electrochemical performance of silicon-based negative electrode materials, and provide the possibility for the development of high energy density lithium-ion batteries.

[0007] The primary purpose of the present invention is to provide a method for preparing porous silicon-carbon composite microspheres.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing porous silicon-carbon composite microspheres comprises the following steps:

[0010] S1, the aqueous solution obtained by mixing CNT-COOH, SiNPs and PS nanoparticles is used as the precursor solution, and the span 80 n-hexadecane solution is used as the continuous phase;

[0011] S2, using microfluidic technology to control, injecting the precursor solution in step S1 as the dispersed phase and the continuous phase into a flow focusing microfluidic device, adjusting the flow rates of the continuous phase and the dispersed phase, so that the dispersed phase is sheared and emulsified by the continuous phase in the microfluidic device to form microemulsion droplets of uniform size, wherein the size of the microemulsion droplets depends on the shear size of the microfluidic device and the flow rate of the internal and external phase fluids, and drying the microemulsion droplets suspended in the continuous phase to obtain microspheres (DMs);

[0012] S3, calcining the microspheres obtained in step S2 under an inert atmosphere to remove the PS nanoparticles and obtain silicon-carbon composite microspheres (Si / CNT MSs).

[0013] Preferably, the mass percentage of the precursor solution in step S1 is 1wt%-5wt%, more preferably 2.5wt%.

[0014] Preferably, in step S1, the mass ratio of CNT-COOH:PS is 1:1.

[0015] Preferably, the mass fraction of the span 80 solution in step S1 is 5wt%-30wt%, more preferably, 25wt%.

[0016] Preferably, the size of the shear cut in the microfluidic technology in step S2 is 15 μm-75 μm, and more preferably, the size of the shear cut is 50 μm.

[0017] Preferably, the drying temperature in step S2 is 50-80° C. and the drying time is 20-30 hours.

[0018] Preferably, the inert atmosphere in step S3 is argon, the calcination temperature is 500-1000° C., the insulation time is 2-4 hours, and the heating rate is 1-5° C. / min.

[0019] The present invention also provides a porous silicon-carbon composite microsphere prepared by the method.

[0020] Preferably, the particle size of the composite microspheres is 8 μm-15 μm.

[0021] The present invention also provides the use of the porous silicon-carbon composite microspheres in preparing negative electrode materials for lithium-ion batteries.

[0022] Preferably, the preparation method of the negative electrode material comprises: uniformly mixing the silicon-carbon composite microspheres, the conductive agent and the binder, coating them on a current collector and drying them; wherein the conductive agent is Super P, and the binder is sodium alginate; calculated by mass percentage, the silicon-carbon composite microspheres are 70-80%, the conductive agent is 10-20%, and the binder is 10-20%.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The silicon-carbon composite microspheres (Si / CNT MSs) prepared by the droplet microfluidic technology of the present invention have controllable structures and uniform sizes, and the preparation technology is simple and efficient. When the composite microspheres are applied to the negative electrode of a lithium-ion battery, since the composite microspheres have a narrow particle size distribution and a rich pore structure, the volume expansion of silicon during the charge and discharge cycle can be effectively alleviated, the integrity of the structure can be ensured, and at the same time, a channel can be provided for ion transport, and the conductivity can be improved, so that the lithium-ion battery can exhibit a higher specific capacity, better rate performance and cycle stability. Therefore, the present invention has important value in promoting the industrialization of silicon-carbon negative electrode materials for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a flow chart for preparing the silicon-carbon composite microspheres of the present invention.

[0026] Figure 2 This is the SEM image of the microspheres (DMs) before calcination in Example 1 of the present invention.

[0027] Figure 3 This is a SEM image of the silicon-carbon composite microspheres of Example 1 of the present invention, wherein: Figure 3 c and 3d are SEM images of the microspheres (DMs) before calcination in Example 1 of the present invention. Figure 3 e is the SEM image of the calcined silicon-carbon composite microspheres.

[0028] Figure 4 This is the XRD diagram of the silicon-carbon composite microspheres in Example 1 of the present invention.

[0029] Figure 5 It is the particle size of the silicon-carbon composite microspheres prepared in Example 1 (Si / CNT MSs-15), Example 4 (Si / CNT MSs-5) and Example 5 (Si / CNT MSs-30) of the present invention.

[0030] Figure 6 This is a graph showing the initial charge and discharge performance of the silicon-carbon composite microspheres prepared in Example 1 (Si / CNT MSs-15), Example 4 (Si / CNT MSs-5) and Example 5 (Si / CNT MSs-30) of the present invention and the silicon-carbon composite material prepared in Comparative Example 1 when used as negative electrode materials in lithium-ion batteries.

[0031] Figure 7 This is a rate performance curve of the silicon-carbon composite microspheres prepared in Example 1 (Si / CNT MSs-15), Example 4 (Si / CNT MSs-5) and Example 5 (Si / CNT MSs-30) of the present invention and the silicon-carbon composite material prepared in Comparative Example 1 used as negative electrode materials for lithium-ion batteries.

[0032] Figure 8This is a cycle performance curve diagram of the silicon-carbon composite microspheres prepared in Example 1 (Si / CNT MSs-15), Example 4 (Si / CNT MSs-5) and Example 5 (Si / CNT MSs-30) of the present invention and the silicon-carbon composite material prepared in Comparative Example 1 when used as negative electrode materials in lithium-ion batteries. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise specified, the experimental methods used in the examples of the present invention are all conventional methods; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified. Figure 1 This is a flow chart of preparing porous silicon-carbon composite microspheres by droplet microfluidics technology. The preparation method is simple and low-cost.

[0035] Example 1

[0036] (1) CNT-COOH, SiNPs and PS nanoparticles were mixed, wherein the mass ratio of CNT-COOH:PS nanoparticles was 1:1, and the amount of SiNPs was 0.125 g each, and 2.5 wt% of precursor A was prepared.

[0037] (2) Prepare a continuous phase 25 wt% span 80 n-hexadecane solution.

[0038] (3) The precursor A obtained in step (1) is injected into a flow focusing microfluidic device as a dispersed phase and the continuous phase obtained in step (2) at the same time. The dispersed phase is shear-emulsified by the continuous phase in the microfluidic device, and the shear opening size is 50 μm to obtain microemulsion droplets.

[0039] (4) Drying the microemulsion droplets obtained in step (3) at 60° C. for 24 h to obtain microspheres (DMs).

[0040] (5) The microspheres obtained in step (4) are placed in an argon atmosphere, calcined at 800° C., kept warm for 2 h, and heated at a rate of 5° C. / min to obtain silicon-carbon composite microspheres (Si / CNT MSs).

[0041] The silicon-carbon composite microspheres are used to prepare negative electrode materials for lithium-ion batteries; wherein the conductive agent is Super P; the binder is sodium alginate; calculated by mass percentage, the silicon-carbon composite microspheres are 80%, the conductive agent is 10%, and the binder is 10%.

[0042] Example 2

[0043] The specific implementation process of this embodiment is the same as the steps of Embodiment 1, the only difference being that the mass percentage of the precursor in step (1) is changed to 1 wt %.

[0044] Example 3

[0045] The specific implementation process of this embodiment is the same as the steps of Embodiment 1, the only difference being that the mass percentage of the precursor in step (1) is changed to 5wt%.

[0046] Example 4

[0047] The specific implementation process of this embodiment is the same as the steps of embodiment 1, except that the size of the cut in step (4) is changed to 15 μm.

[0048] Example 5

[0049] The specific implementation process of this embodiment is the same as the steps of Embodiment 1, the only difference being that the size of the cut in step (4) is changed to 75 μm.

[0050] Example 6

[0051] The specific implementation process of this embodiment is the same as the steps of Embodiment 2, the only difference being that the size of the cut in step (4) is changed to 15 μm.

[0052] Example 7

[0053] The specific implementation process of this embodiment is the same as the steps of Embodiment 2, the only difference being that the size of the cut in step (4) is changed to 75 μm.

[0054] Example 8

[0055] The specific implementation process of this embodiment is the same as the steps of Embodiment 3, the only difference being that the size of the cut in step (4) is changed to 15 μm.

[0056] Example 9

[0057] The specific implementation process of this embodiment is the same as the steps of Embodiment 3, the only difference being that the size of the cut in step (4) is changed to 75 μm.

[0058] Comparative Example 1

[0059] Silicon powder and carbon nanotubes were mixed and ground in a mass ratio of 6:4 to obtain a silicon-carbon mixture (Si / CNT).

[0060] Experimental example

[0061] Preparation of lithium-ion battery negative electrode and lithium-ion battery: The silicon-carbon composite microsphere material obtained in Example 1 is mixed evenly with the conductive agent and the binder according to the mass percentage, coated on the current collector, and dried to obtain the lithium-ion battery negative electrode material. The positive electrode and the negative electrode, the electrolyte, and the diaphragm are assembled into a lithium-ion battery, and then the material characterization and electrochemical testing are carried out. Among them, lithium metal is used as the negative electrode, the positive electrode is silicon-carbon microspheres, the diaphragm is an industrial polypropylene diaphragm, the electrolyte is a LiPF6 solution with a concentration of 1 mol / L, and the EC / DEC mixed solution of 1:1 (volume ratio) is used as the solvent.

[0062] Attached Figure 2 This is a SEM image of the microspheres (DMs) prepared in step (4) of Example 1. As can be seen from the image, before calcination, the particle size of the microspheres is relatively uniform, about 8 μm.

[0063] Microscopic observation was performed under a scanning electron microscope. Figure 3 As shown, Figures c and d are microspheres (DMs) before calcination, and Figure e is a silicon-carbon composite microsphere after calcination, with abundant honeycomb-like macropores on its surface. These macropores are left over after the PS nanoparticles are calcined, and their size is comparable to that of the PS nanoparticles, about 250nm. The design of the porous structure can not only reduce the volume change of silicon during the cycle, but also provide a transport channel for ions and improve conductivity, so that the lithium-ion battery exhibits excellent electrochemical performance.

[0064] Figure 4 This is the X-ray diffraction test diagram of the silicon-carbon composite microspheres prepared in Example 1. The wide band of Si / CNT MSs in the figure ranges from 20° to 30°. The presence of the wide band indicates that DMs forms amorphous SiOx after calcination. The formation of this substance can reduce the degree of pulverization of the negative electrode during the charge and discharge process, ensure the integrity of the negative electrode material structure, and improve the cycle stability of the battery.

[0065] Figure 5 From the particle size distribution of the silicon-carbon composite microspheres prepared in Example 4, Example 1 and Example 5, respectively, it can be seen that the particle size of the silicon-carbon composite microspheres prepared using a 15 μm shear cut is mainly concentrated at 5 μm, the particle size of the silicon-carbon composite microspheres prepared using a 50 μm shear cut is mainly concentrated at 15 μm, and the particle size of the silicon-carbon composite microspheres prepared using a 75 μm shear cut is mainly concentrated at 30 μm.

[0066] Figure 6 From the initial charge and discharge diagrams of the silicon-carbon composite microspheres with average particle sizes of 5 μm, 15 μm, and 30 μm prepared in Example 4, Example 1, and Example 5, respectively, and the silicon-carbon composite material prepared in Comparative Example 1, it can be seen that the initial coulombic efficiency of the silicon-carbon composite microspheres prepared in Example 1 is 94.5%, while the coulombic efficiency of the silicon-carbon composite material prepared in Comparative Example 1 is only 79.1%.

[0067] Figure 7 The rate performance diagrams are for silicon-carbon composite microspheres with average particle sizes of 5 μm, 15 μm, and 30 μm prepared in Example 4, Example 1, and Example 5, respectively, and the silicon-carbon composite material prepared in Comparative Example 1. The silicon-carbon composite microspheres with an average particle size of 15 μm prepared in Example 1 still have a specific capacity of more than 500 mAh / g at a current density of 5 A / g, while the specific capacity of the silicon-carbon composite material prepared in Comparative Example 1 decays to less than 500 mAh / g at a current density of 2 A / g, which indicates that the structural design of the composite material can alleviate the volume expansion of silicon and enable the battery to exhibit better rate performance.

[0068] Figure 8 The figure is a cycle performance diagram of the silicon-carbon composite material prepared in Example 4, Example 1 and Example 5 with an average particle size of 5μm, 15μm, 30μm, respectively, and the silicon-carbon composite material prepared in Comparative Example 1. The battery was activated at 0.1A / g for the first two cycles, and then subjected to a long cycle at a current density of 1A / g. As can be seen from the figure, the silicon-carbon composite microspheres with an average particle size of 15μm prepared in Example 1 can achieve more than 500 cycles at a current density of 1A / g without capacity decay, while the specific capacity of the silicon-carbon composite material almost approaches 0 after 193 cycles, indicating that the silicon-carbon composite material can buffer the volume expansion of silicon to ensure the stability of the structure, thereby improving the electrochemical performance of the battery.

[0069] Obviously, the specific implementation scheme described above is only a further detailed description of the purpose, technical scheme and beneficial effects of the present invention. It should be understood that the above is only a specific example of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Application of porous silicon-carbon composite microspheres in improving rate performance and cycle stability of lithium-ion batteries, characterized in that: The composite microspheres are prepared by the following steps: S1, using a mixed aqueous solution of CNT-COOH, SiNPs and PS nanoparticles as a precursor solution, wherein the precursor solution is a dispersed phase and a span 80 n-hexadecane solution is a continuous phase; S2, using microfluidic technology to cause the dispersed phase in step S1 to be shear-emulsified by the continuous phase to form microemulsion droplets, and drying the microemulsion droplets suspended in the continuous phase to obtain microspheres; S3, calcining the microspheres obtained in step S2 under an inert atmosphere to remove the PS nanoparticles to obtain silicon-carbon composite microspheres; The particle size of the porous silicon-carbon composite microspheres is 8 μm-15 μm.

2. The use according to claim 1, characterized in that: The mass percentage of the precursor solution in step S1 is 1wt%-5wt%, wherein the mass ratio of CNT-COOH:PS is 1:

1.

3. The use according to claim 1, characterized in that: The mass fraction of the solution of span 80 in step S1 is 5wt%-30wt%.

4. The use according to claim 1, characterized in that: The size of the shear cut in the microfluidic technology described in step S2 is 15 μm-75 μm.

5. The use according to claim 1, characterized in that: The drying temperature in step S2 is 50°C-80°C and the drying time is 20h-30h.

6. The use according to claim 1, characterized in that: In step S3, the inert atmosphere is argon, the calcination temperature is 500°C-1000°C, the insulation time is 2h-4h, and the heating rate is 1-5°C / min.

7. The use according to claim 1, characterized in that: The negative electrode material of the lithium ion battery is prepared by the following method: the porous silicon-carbon composite microspheres, the conductive agent and the binder are evenly mixed, coated on a current collector and dried; wherein the conductive agent is Super P, the binder is sodium alginate, and calculated by mass percentage, the silicon-carbon composite microspheres are 70%-80%, the conductive agent is 10%-20%, and the binder is 10%-20%.